The effect of interrupting sedentary behavior on the cardiometabolic health of adults with sedentary occupations a pilot study - Dunning, J.; McVeigh, Joanne; Goble, D.; Meiring, R. (Lippincott Williams and Wilkins, 2018)
Copyright ß 2018 American College of Occupational and Environmental Medicine Objective: The aim of this study was to determine whether mobile phone text messages could modify objectively measured sedentary behavior and cardiometabolic health in office workers. Methods: Nine males and 12 females [mean (SD): 27.5 (5.7) years, 23.8 (2.8) kg/m2] were assigned to a control (CON) or intervention (PROMPT) group. PROMPT received an activity-promoting text message during office hours. Participants wore an actiGraph and activPAL accelerometer for 7 days during and after the intervention. Blood pressure, lipid, and metabolic profiles were measured before and after the intervention. Results: PROMPT sat less [mean (95% confidence interval, 95% CI): 4.9 (4.4 to 5.4) hours/day] than CON [6.0 (5.5 to 6.4) hours/day; P ¼ 0.04] during the message-receiving period. There was no difference between groups after the intervention and for the other activity variables. There were no changes in cardiometabolic health markers following the intervention. Conclusion: Sitting time was lower during the message-receiving period, but the difference between groups was no longer apparent after the intervention.